Spectrum of poisoning in Bundelkhand region - Aparna Shankwar; Ankur Kumar (Asian Journal of Medical Sciences, 2024)
Background: In Bundelkhand region, 15–18% patients who are attended in the emergency setting comprises poisoning and 60–70% of which are agriculture-based poisons due to its easy accessibility. Aims and Objectives: The aim of this study was to see spectrum of poisoning in Bundelkhand region. Materials and Methods: The prospective non-randomized study was done in Maharani Laxmi Bai Medical College, Jhansi, between December 2020 and October 2022, including 500 patients applied for treatment of different poisoning. Results: In our study, total 500 cases of poisoning were taken. As per found data, majority of patients were found in 17–30 years of age group 202 (40.4%) followed by 31–40 years of age group 157 (31.4%). Minimum 19 (3.8%) cases were found in 61–70 years of age group and 0 case in >70 years of age group. Majority of patients were found male, i.e., 281 (56.2%) and the rest 219 (43.8%) were females. According to finding of our study, maximum mortality rate was found due to Stone hair dye, i.e., 100% followed by Celphos 35.54%, Insecticidal 26.92%, and Alcoholic intoxication 22.22%. As per our study, major cause of taking poison, maximum number of patients were found in marital discord 108 (21.6%) followed by family problems, i.e., 75 (15%), which is similar to separation/death of family member, that is, 74 (14.8%). Conclusion: Concerned authorities should think about substitute of aluminum phosphide, which would be less toxic for human being and concerned authority should ban availability of aluminum phosphide (Celphos) in market.